Single-Board Computer for Affordable Personal Data Storage Server - Andika Candra Jaya (Institute of Computer Science (IOCS), 2021)
The growing concerns of cloud storage privacy would necessitate local network storage. We are proposing to build do-it-yourself Data Storage server and test its cost-effectiveness. We are comparing homebrew data storage server against pre-built Network-Attached Storage and Cloud Storage providers. We conclude that using homebrew network storage server is slightly more cost effective albeit not as user-friendly to set up. Our recommendation is for user to build one and we provided the guide.